CRISPR-Cas9 editing of TNFAIP3 variants in salivary gland epithelial cells to study Sjögren’s disease pathogenesis - Ghosh, Subhashis; Tu, Qisheng; Zhu, Zoe Xiaofang; Panginikkod, Sreelakshmi; Chen, Jake Jinkun (Frontiers in Genome Editing, 2025)
Sjögren’s disease (SD) is a systemic autoimmune disease that particularly affects the salivary and lacrimal glands, causing sicca symptoms. Genetic polymorphism in the TNFAIP3 gene has been implicated in the pathogenesis of SD. In this study, we aimed to functionally determine the impact of two specific single-nucleotide polymorphisms (SNPs) in TNFAIP3, rs6920220 (G/A) and rs2230926 (T/C/G), on the pathogenesis of SD. Using CRISPR-Cas9, we edited human salivary gland epithelial cells (SGECs) to incorporate TNFAIP3 SNPs rs6920220 (G/A) and rs2230926 (T/C/G) and co-cultured them with Jurkat cells. We performed assays to examine gene expression, inflammatory cytokine levels, and related signaling pathways to investigate the effects of these genetic variants on TNFAIP3 function and cellular response. Our results demonstrated that these SNPs reduced TNFAIP3 expression, increased NF-κB activation, and elevated pro-inflammatory cytokine production. These findings provide strong evidence for the functional significance of these genetic variants in the pathogenesis of SD and underscore the utility of CRISPR-Cas9 technology in elucidating genetic contributions to autoimmune disorders.